2008
DOI: 10.1094/pdis-92-2-0247
|View full text |Cite
|
Sign up to set email alerts
|

Population Variation of Apple Scab (Venturia inaequalis) Isolates from Asia and Europe

Abstract: Apple scab, caused by Venturia inaequalis, is one of the most of damaging diseases worldwide on apple and currently is managed mainly by scheduled applications of fungicides. Understanding pathogen population structure is important for breeding and deployment of resistant cultivars. Isolates of V. inaequalis were sampled from a number of cultivars in China, India, and the United Kingdom to estimate differences in pathogen populations. Amplified fragment length polymorphism (AFLP) markers were used to genotype … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 28 publications
5
26
0
Order By: Relevance
“…; Xu et al. , ) have observed low genetic differentiation in various V. inaequalis populations and our results confirm these reports.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…; Xu et al. , ) have observed low genetic differentiation in various V. inaequalis populations and our results confirm these reports.…”
Section: Discussionsupporting
confidence: 92%
“…Parisi et al (2004) reported 87% European V. inaequalis population to overcome Rvi1, and the present investigation confirms over-dominance of such isolates (>83% isolates) in the valley. The high susceptibility of cultivar Royal Gala and Golden Delicious toward Indian isolates observed in this study is in agreement with that of Xu et al (2008). Few workers have reported the presence of races in different parts of world (Shay and Williams 1956;Heaton et al 1991;Bus et al 2011), and the present report about the presence of these races in Kashmir valley is the first such study from India.…”
Section: Pathogenic Variabilitysupporting
confidence: 90%
See 3 more Smart Citations